PAUL'S DAMASCUS ROAD EXPERIENCE AND ITS RELEVANCE TO PASTORAL MINISTRY IN METHODIST CHURCH NIGERIA IN LAGOS (2014)
Paul’s Damascus road experience, which refers to his conversion and call, is central to the success of his ministry. Existing studies on this remarkable experience have focused more on controversies surrounding the unusual nature of the event and its veracity than on its contribution to the success of Paul’s ministry and its relevance to contemporary churches. This study, therefore, investigated the interaction between Paul’s Damascus road experience (Acts 9:1-19, 22:4-16, 26:12-18; Galatians 1:1-17) and his pastoral ministry with a view to establishing their relevance to pastoral ministry in Methodist Church Nigeria (MCN) in Lagos. The study was premised on Abogunrin’s theory of transformative power, which posits that the gospel possesses the power to regenerate and transform an individual into an effective agent of change. Martin’s grammatico-historical approach to biblical exegesis was used to elicit data from selected biblical texts. In-depth interviews were conducted with purposively selected clergy (56: seven from each diocese of eight Methodist dioceses in Lagos State) and laity (56: seven from each diocese). Copies of a questionnaire were administered to 454 randomly selected clergy and laity. While qualitative data were subjected to exegetical analysis; quantitative data were analysed using percentage. Paul’s conversion experience was revelatory and transforming in his life. It was described as a divine revelation in MCN 2006 Constitution. The event validated his call to ministry, which reflected in the success of his pastoral ministry unlike some clergy in MCN without conversion experience (clergy 82.5% and laity 78.1%) which consequently led to ignorance of their call, poor admission procedure into ministry and godfatherism as affirmed by 15.7% of the respondents. The event shaped Paul’s theology in terms of his understanding of Christ as both the Messiah and the end of the law, and the divine intention to incorporate Gentiles into the people of God by faith. Conversely, the pastoral ministry of MCN is characterised by distorted theology arising from poor study of the scriptures (29.6%) and lack of missionary vision (13.0%). The Damascus road experience that informed Paul’s teachings on the Jewish concept of reconciliation and self-sacrificing pastoral activities contrasts with lack of knowledge about salvation (40.7%) and poor sacrificial pastoring among MCN clergy. Some unconverted ministers in Paul’s churches and MCN broke away to found their own ministries. The effects of these on Paul’s churches were envying and fixed parties while there were misplaced priorities, unhealthy rivalry and non-compliance with the resolutions of the church in MCN. In addition, the clergy (96.8%) and the laity (92.1%) attributed ineffectiveness in the pastoral ministry of MCN to lack of conversion experience, and blamed unconverted ministers for the spiritual, numerical and financial stagnation of the Church. Contrary to the experience in Methodist Church Nigeria in Lagos, Paul’s Damascus road experience impacted positively on the success of his pastoral ministry. The Church, therefore, needs to review its doctrinal operation to guarantee genuine conversion and call into the pastoral ministry. This is imperative for a productive Christian ministry needed in the contemporary Nigerian religious terrain.